"The lighter side" of TOEFL : (United States Department of State, 2005)
The book includes the activities reinforce vocabulary or give students practice listening, thinking, speaking and writing, but the underlying goal of all activities is to produce a smile and awareness that communicating in English has a lighter side and a potential for fun.